Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.5455/javar.2019.f340
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial efficacy of ethanolic extract of Camellia sinensis and Azadirachta indica leaves on methicillin-resistant Staphylococcus aureus and shiga-toxigenic Escherichia coli

Abstract: Objective: This study aims at investigating the antibacterial potential of ethanolic extract of Camellia sinensis (common name: Green tea) and Azadirachta indica (common name: Neem) leaves on methicillin-resistant Staphylococcus aureus (MRSA) and shiga-toxigenic Escherichia coli (STEC). Materials and Methods: Fresh leaves were processed and extracted by 99% ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
(34 reference statements)
1
15
1
Order By: Relevance
“…19 The antibacterial properties of green tea extract were also verified by Zihadi et al, that reported MIC values of 15.625 and 31.25 mg.mL −1 against methicillin-resistant Staphylococcus aureus (MRSA) and shiga-toxigenic Escherichia coli (STEC), respectively. 38 On the other hand, Orak et al, using the same agar well-diffusion method used in the present work for microbiological analysis, also did not verified any antimicrobial activity of green tea against E. coli ATCC 25922. 39 But an inhibition halo was observed in this work for S. aureus ATCC 25923.…”
Section: Resultscontrasting
confidence: 62%
“…19 The antibacterial properties of green tea extract were also verified by Zihadi et al, that reported MIC values of 15.625 and 31.25 mg.mL −1 against methicillin-resistant Staphylococcus aureus (MRSA) and shiga-toxigenic Escherichia coli (STEC), respectively. 38 On the other hand, Orak et al, using the same agar well-diffusion method used in the present work for microbiological analysis, also did not verified any antimicrobial activity of green tea against E. coli ATCC 25922. 39 But an inhibition halo was observed in this work for S. aureus ATCC 25923.…”
Section: Resultscontrasting
confidence: 62%
“…In contrast, the Stephania suberosa Forman extract (SSE) against ampicillin-resistant S. aureus showed higher MIC with 4 mg/ml [34]. High MIC was also noted in the olive oil polyphenol extract [41], Camellia sinensis, and Azadirachta indica leaves extracts [42] against S. aureus. This indicates that Photorhabdus extracts are more effective than SSE, olive oil polyphenol extract, Camellia sinensis, and Azadirachta indica leaves extracts.…”
Section: Plos Onementioning
confidence: 99%
“…For example, Zihadi et al (2019) have investigated the antibacterial potential of ethanolic extract of Green tea (Camellia sinensis) and Neem (Azadirachta indica) leaves on methicillin-resistant Staphylococcus aureus (MRSA) and Shiga-toxigenic Escherichia coli (STEC). Results obtained by Zihadi et al (2019) revealed that the maximum zone diameter of inhibition value was observed for green tea against MRSA (7.5 mm) and minimum for neem (4.9 mm). Moreover, the highest zone diameter of inhibition against STEC was also for green tea and the combination of green tea and neem (4.5 mm).…”
Section: Resultsmentioning
confidence: 99%